Women Safety Security System Using Raspberry Pi Pico - M, Naveen; Sai Kumar, G; Puroshotham Naik, R.; Damodhar, .K. (International Journal of Psychosocial Rehabilitation, 2019)
In today’s world women safety has become a major issue as they cannot step out of their house at any given time due to fear of physical abuse and violence. Now these can be brought to an end with the help of a women safety device. This safety device consists of a RASPBERRY PICO controller, emergency button switch. On sensing the emergency situation this device provides the current location of women and sense it to emergency contact through GSM MODULE. This safety device includes a sensor like heartbeat sensor, whenever pulse increases SMS with location will be sent to the person and and dht11 sensor , any temperature increases it will give buzzer alert . Push button is used to get intimated for help any attacking person due to which there is a chance for the women to escape. GPS receiver gets location information from satellite in the form of latitude and longitude. The GSM modem sends an SMS to the pre-defined mobile number. When a woman is in danger she can press the switch which is with her. By pressing the switch the entire system will be activated. Then immediately the SMS will be sent to the person with location using GSM and GPS which can be traced from the google maps.